2000
DOI: 10.1038/sj.ijo.0801375
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-reported weight and height in the French GAZEL cohort

Abstract: OBJECTIVE: To examine the validity of self-reported weight and height and the resulting body mass index (BMI), and to explore the associations between demographic, socioeconomic, and health-related factors on the one hand and bias in self-reported weight and height on the other, in order to determine the groups most likely to exhibit bias. DESIGN: Prospective cohort study. SUBJECTS: 7350 middle-aged subjects, 5445 men and 1905 women, from the GAZEL cohort, who have been followed up since 1989 and work at the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
382
14
33

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(465 citation statements)
references
References 26 publications
36
382
14
33
Order By: Relevance
“…It is known that subjects tend to underestimate weight and to overestimate height (Niedhammer et al, 2000;Spencer et al, 2002;Avila-Funes et al, 2004). However, adding up the mean discrepancies between self-reported and measured weight and height found in one study from France (Niedhammer et al, 2000), whose population is similar to the Italian one in terms of BMI (Martinez et al, 1999), the overall prevalence of subjects with a BMI X25 kg/m 2 would be 43.4%, still considerably lower than the prediction of 59% in 2006 in Italy (Anonymous, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that subjects tend to underestimate weight and to overestimate height (Niedhammer et al, 2000;Spencer et al, 2002;Avila-Funes et al, 2004). However, adding up the mean discrepancies between self-reported and measured weight and height found in one study from France (Niedhammer et al, 2000), whose population is similar to the Italian one in terms of BMI (Martinez et al, 1999), the overall prevalence of subjects with a BMI X25 kg/m 2 would be 43.4%, still considerably lower than the prediction of 59% in 2006 in Italy (Anonymous, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the study design included a reliance on self-reported height and weight, given that validation studies show that women tend to under-report their weight, particularly if they are obese. 38,39 However, if the amount of bias remains fairly consistent, as shown in a reliability study of the Nurses Health cohort, 40 weight change may be a less biased measure than weight. Further studies are needed on the validity of weight change measures.…”
Section: Weight Control Practices and 2-year Weight Changementioning
confidence: 99%
“…The SR-MD divergence is larger among women than among men, the less educated the individuals are and the higher their BMI according to MD (Rowland, 1990;Niedhammer et al, 2000;Kuczmarski et al, 2001;Villanueva, 2001). It varies by age (Niedhammer et al, 2000;Kuczmarski et al, 2001) and occupational status (Bostrom and Diderichsen, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Studies according to whether SR data of body weight and height are comparable to measurement devices (MD) data about body weight and height have been carried out (e.g. Niedhammer et al, 2000;Villanueva, 2001;Wada et al, 2005). However, there are considerable limitations according to cultural aspects or according to the samples -some of them are no general population samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation